Emerging Insight Into the Role of Circadian Clock Gene BMAL1 in Cellular Senescence - Zhang, Wenqian; Xiong, Yuan; Tao, Ranyang; Panayi, Adriana C.; Mi, Bobin; Liu, Guohui (Frontiers in Endocrinology, 2022)
Cell senescence is a crucial process in cell fate determination and is involved in an extensive array of aging-associated diseases. General perceptions and experimental evidence point out that the decline of physical function as well as aging-associated diseases are often initiated by cell senescence and organ ageing. Therefore, regulation of cell senescence process can be a promising way to handle aging-associated diseases such as osteoporosis. The circadian clock regulates a wide range of cellular and physiological activities, and many age-linked degenerative disorders are associated with the dysregulation of clock genes. BMAL1 is a core circadian transcription factor and governs downstream genes by binding to the E-box elements in their promoters. Compelling evidence has proposed the role of BMAL1 in cellular senescence and aging-associated diseases. In this review, we summarize the linkage between BMAL1 and factors of cell senescence including oxidative stress, metabolism, and the genotoxic stress response. Dysregulated and dampened BMAL1 may serve as a potential therapeutic target against aging- associated diseases.